2019
DOI: 10.17576/3l-2019-2502-02
|View full text |Cite
|
Sign up to set email alerts
|

Binary Logistic Regression Analysis of Instructional Leadership Factors Affecting English Language Literacy in Primary Schools

Abstract: This paper discusses the factors contributing to student achievement in English language literacy in primary schools within Sibu division, Sarawak, Malaysia. The study involved 694 teachers who taught in 105 lower primary schools. Binary logistic regression was applied to predict the instructional leadership's influence on student achievement in literacy. The findings revealed that one dimension of instructional leadership-supervising and evaluating instruction-emerged as strong predictors of literacy. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Several of the strategies derived from the findings include teachers' early intervention, teaching students appropriately, having clear learning outcomes, and employing a variety of teaching methods to transmit knowledge to students. In contrast, previous research by Sio and Ismail [21] found that teacher efficacy is the most important factor in improving students' literacy and numeracy skills. This could be because teachers are good at using different teaching methods to improve their students' reading and math skills.…”
Section: Discussioncontrasting
confidence: 61%
“…Several of the strategies derived from the findings include teachers' early intervention, teaching students appropriately, having clear learning outcomes, and employing a variety of teaching methods to transmit knowledge to students. In contrast, previous research by Sio and Ismail [21] found that teacher efficacy is the most important factor in improving students' literacy and numeracy skills. This could be because teachers are good at using different teaching methods to improve their students' reading and math skills.…”
Section: Discussioncontrasting
confidence: 61%
“…Binary logistic regression was used to examine the brand loyalty in buying tea. Many studies [14,15,16] have utilized binary logistic regression to find the relationship between binary response with predictor variables [17]. The response variable, brand loyalty status consisted of two categories as "brand loyal" and "non-brand loyal".…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed using both SPSS and SAS software. Many studies [12,13,14] have utilized binary logistic regression to find the relationship between binary response with predictor variables [15]. The response variable, fertilizer application status, consisted of two categories as "applying fertilizer" and "not applying fertilizer" denoted by Y = 1 (applying) and Y = 0 (not applying).…”
Section: Discussionmentioning
confidence: 99%